THE GEOSOPHICAL SIGNIFICANCE OF MOUNTAINS IN KYRGYZ SELF-AWARENESS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article presents a geosophical understanding of the importance of mountains in the self-consciousness of the Kyrgyz people, where the sacred geography of the mountains ensured the maintenance of ethnic and cultural self-awareness of the Kyrgyz, provided a metaphysical connection of times and promoted the spiritual transit of memory through epic traditions. The study then captures the wide and multifaceted influence of the mountainous environment, reflected in mythological legends, the philosophical heritage of the Zaman Akyns, the work of Aitmatov, and also semantically embodied in the ethnonym “Kyrgyz”, where “kyr” means “mountain”, “peak” or “elevation” and “giz”, which, according to numerous According to their interpretative positions, they are understood as a people. As a result, the ethnonym “Kyrgyz” is interpreted as “mountain people” or “mountain people”. The main focus of the work is devoted to the deep and indissoluble spiritual connection of the Kyrgyz people with the space of the mountains of Eurasia, which sheds light on the secrets of the ethnocultural tradition of the Kyrgyz. Among other things, the author of the study presents a curious metaphysical view that reveals the geosophical significance of mountains in the sacred geography of Eurasia, where the Turan mountains are the habitat of deities, a concentrated zone of sacred traditions and a territory where the spiritual experience of bygone eras is preserved.
Keywords: Geosophy; mountains; Eurasia; self-awareness; sacred geography; ethnonym “Kyrgyz”; legend; cosmic environment.